Metal-free synthesis of gem-difluorinated heterocycles from enaminones and difluorocarbene precursors. Issue 21 (22nd February 2022) - Wang, Fei; Fu, Rui; Chen, Jie; Rong, Jiaxin; Wang, Enfu; Zhang, Jian; Zhang, Zhengyu; Jiang, Yaojia
Abstract : A cascade strategy to synthesise gem -difluorinated 2 H -furans from reactions of BrCF2 CO2 Et with enaminones has been described. The reactions work efficiently for a broad substrate scope and tolerate a variety of functional groups under very mild metal-free conditions. Abstract : A cascade strategy to synthesise gem -difluorinated 2 H -furans from reactions of BrCF2 CO2 Et with enaminones has been described. The reactions tolerate a wide variety of functional groups under metal-free conditions. An active aminocyclopropane is proposed to be a key intermediate through the cyclopropanation of difluorocarbene with enaminones, which further triggers a regioselective C–C bond cleavage in situ to afford the corresponding gem -difluorinated 2 H -furans.